2017
DOI: 10.21909/sp.2017.03.741
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Emotional Facial Expressions in Alexithymia

Abstract: Alexithymia is a personality trait which is associated with difficulties in identifying and verbalizing emotions. Previous studies have shown a significant association between alexithymia and a lack of ability to decode emotional facial expressions. Three groups of university students (N = 1645) were formed by splitting the sample based on Toronto Alexithymia Scale (TAS-20) scores. All participants performed an emotional expression recognition task, using the "Reading the Mind in the Eyes'' method. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The available evidence highlights contrasting results regarding the presence of difficulties in the recognition of others' affective mental states in individuals with alexithymia. Indeed, although some previous studies found significant relationships between alexithymia and impairments in RMET performance (Gökçen et al, 2016;Martinez-Sanchez et al, 2017;Oakley et al, 2016;Swart et al, 2009), others found mixed results (Demers and Koven, 2015). In particular, the study of Demers and Koven (2015) found that only the EOT factor of the TAS-20 significantly predicted impaired performance on the RMET.…”
Section: Discussionmentioning
confidence: 95%
“…The available evidence highlights contrasting results regarding the presence of difficulties in the recognition of others' affective mental states in individuals with alexithymia. Indeed, although some previous studies found significant relationships between alexithymia and impairments in RMET performance (Gökçen et al, 2016;Martinez-Sanchez et al, 2017;Oakley et al, 2016;Swart et al, 2009), others found mixed results (Demers and Koven, 2015). In particular, the study of Demers and Koven (2015) found that only the EOT factor of the TAS-20 significantly predicted impaired performance on the RMET.…”
Section: Discussionmentioning
confidence: 95%
“…Alexithymia, reported in both fibromyalgia [23,36,38,76,87,103,104] and obesity [20,22,[32][33][34][35], may be described not only as a marker of global emotional difficulties [105], but also as a general failure of interoception (i.e., the ability in perceiving and recognizing the internal state of the body [20,[106][107][108]). In other words, because of the presence of alexithymia, individuals might misattribute the origin of their bodily experience [38] and/or showed difficulties in converting own somatic sensations in feelings and cognitions [106]; this difficulty may in turn interfere also with the ability to identify others' emotional states [76,[109][110][111][112][113][114], with effect on the emotional contagion and empathy (as preliminary observed in fibromyalgia [23,115] and obesity [116]).…”
Section: Alexythimic Traits and Interoceptionmentioning
confidence: 99%
“…Because these individuals cannot properly identify their negative emotions, they have difficulties in depleting and neutralizing these emotions. The lack of emotion regulation ability intensifies the negative disabling emotions [33]. The more deficiency in identifying and differentiating the emotions, the more severe the symptoms of phobia and depression.…”
Section: Discussionmentioning
confidence: 99%